2009
DOI: 10.1063/1.3077160
|View full text |Cite
|
Sign up to set email alerts
|

MoO 3 surface passivation of the transparent anode in organic solar cells using ultrathin films

Abstract: International audienceAn original surface passivation technique of indium tin oxide (ITO) used as anode in organic solar cells is proposed. We demonstrate that a thin MoO3 film (3.5 +/- 1 nm) at the interface ITO/organic donor allows improving significantly the devices' performances. The devices are based on the multiheterojunction structure copper phthalocyanine (CuPc)/fullerene (C-60)/aluminum tris(8-hydroxyquinoline) (Alq(3)). The deposition of MoO3 onto ITO improves the charge transfer from CuPc to ITO. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 34 publications
4
95
0
Order By: Relevance
“…Metal oxides were used as buffer layer under the anodes to increase their work function (WF), and enhance hole transport across the organic/electrode interface. [11][12][13][14][15][16][17] The energy level alignment has been extensively argued in many reports; [18][19][20][21][22] several models have been proposed to understand their interfacial electronic structures. The electrostatic model based on the density of states in the organic semiconductor predicted the band-bending in organic semiconductors for different work functions.…”
mentioning
confidence: 99%
“…Metal oxides were used as buffer layer under the anodes to increase their work function (WF), and enhance hole transport across the organic/electrode interface. [11][12][13][14][15][16][17] The energy level alignment has been extensively argued in many reports; [18][19][20][21][22] several models have been proposed to understand their interfacial electronic structures. The electrostatic model based on the density of states in the organic semiconductor predicted the band-bending in organic semiconductors for different work functions.…”
mentioning
confidence: 99%
“…The has been used as buffer layer between the anode and the organic electron donor since it has been shown that it is very efficient in improving the hole collection and OPV cells performances [15]. It can be seen in Table 1 and Fig.…”
Section: Organic Photovoltaic Cells Using Azo/in 2 O 3 and Fto/in 2 Omentioning
confidence: 91%
“…The introduction of a thin anode buffer layer (ABL) between the ITO and the ED induces a significant improvement of the device efficiency [ 8]. For instance, we have shown that Au [ 9] and MoO x [10] allow achieving this goal, by simple vacuum deposition of an ultra -thin gold film or of a thin MoO x film when CuPc is the ED. Here, the effects of a gold or MoO x ABL onto the ITO anode are studied using ED with different HOMO.…”
Section: Introductionmentioning
confidence: 97%
“…The thicknesses were 40 nm, 9 nm and 130 nm for C 60 , BCP and Al respectively. The ABL thicknesses were 0.5 nm [9] and 3.5 nm [10] for Au and MoO 3 respectively. The thickness of the different ED layers have been optimized, they are 35 nm for CuPc, 25 nm for pentacene, 20 nm for DBP and T3PM.…”
Section: Methodsmentioning
confidence: 99%